European Society for Radiotherapy and Oncology and European Organisation for Research and Treatment of Cancer consensus on re-irradiation: definition, reporting, and clinical decision making. Issue 10 (October 2022) - Andratschke, Nicolaus; Willmann, Jonas; Appelt, Ane L; Alyamani, Najlaa; Balermpas, Panagiotis; Baumert, Brigitta G; Hurkmans, Coen; Høyer, Morten; Langendijk, Johannes A; Kaidar-Person, Orit; van der Linden, Yvette; Meattini, Icro; et al.
Summary: Re-irradiation can be considered for local recurrence or new tumours adjacent to a previously irradiated site to achieve durable local control for patients with cancer who have otherwise few therapeutic options. With the use of new radiotherapy techniques, which allow for conformal treatment plans, image guidance, and short fractionation schemes, the use of re-irradiation for different sites is increasing in clinical settings. Yet, prospective evidence on re-irradiation is scarce and our understanding of the underlying radiobiology is poor. Our consensus on re-irradiation aims to assist in re-irradiation decision making, and to standardise the classification of different forms of re-irradiation and reporting. The consensus has been endorsed by the European Society for Radiotherapy and Oncology and the European Organisation for Research and Treatment of Cancer. The use of this classification in daily clinical practice and research will facilitate accurate understanding of the clinical implications of re-irradiation and allow for cross-study comparisons. Data gathered in a uniform manner could be used in the future to make recommendations for re-irradiation on the basis of clinical evidence. The consensus document is based on an adapted Delphi process and a systematic review of the literature was done according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA).